Evaluating Triazole-Substituted Pyrrolopyrimidines as CSF1R Inhibitors - Srinivasulu Cherukupalli; Jan Eickhoff; Carsten Degenhart; Peter Habenberger; Anke Unger; Bård Helge Hoff; Eirik Sundby (Molecules)
6-Aryl-7H-pyrrolo[2,3-d]pyrimidin-4-amines have promising properties as colony-stimulating factor 1 receptor (CSF1R) inhibitors. Inspired by these antagonists, two series of 1,2,3-triazole analogues (28 compounds) were synthesized and evaluated as CSF1R inhibitors. Enzymatic IC50 profiling showed that 27 of the 28 derivatives had lower IC50 than the reference drug PLX-3397. Three derivatives displayed CSF1R Ba/F3 cellular IC50 well below 1 µM. Profiling of the most promising triazole analogue (compound 27a) toward a panel of kinases reveals a high selectivity for CSF1R with respect to its family kinases, but 27a also inhibits ABL, SRC, and YES kinases. Molecular docking of 27a toward two CSF1R X-ray structures identified two different ligand-inverted binding poses, which triggers interest for further investigations.